How to Build Employee Motivation and Performance - Nazifah Husainah (Greenation Research & Yayasan Global Resarch National, 2023)
The purpose of this research is to assess how leadership style, organizational commitment, and motivation impact the performance of employees in the Manufacturing Industries of West Kalimantan. The study utilizes a combination of descriptive and explanatory surveys, with a sample size consisting of 450 employees. Path analysis is the chosen statistical analysis method for this research. The results of the study demonstrate that leadership style, organizational commitment, and work motivation collectively exert a positive and substantial influence on employee performance within the Manufacturing Industries of West Kalimantan. Additionally, it is apparent that motivation plays a prominent role in shaping employee performance.